IPMI Institute Book Chapter Event on the AI Revolution as To Shape the Industries, Cities, and Education - Lahuddin, Abdul Haris; Nawangwulan, Irma M; Anantadjaya, Samuel PD; Nurfadilah, Dety (Journal of Sustainable Community Development (JSCD), 2025)
The rapid advancement of artificial intelligence (AI) has revolutionized various aspects of human life, from transforming industries to reimagining cities and reshaping education systems. In term of the digital era, understanding the role of AI becomes crucial for harnessing its potential to drive innovation and create sustainable solutions for the challenges of the future. The book entitled “Artificial Intelligence Revolution: Shaping Industries, Cities, and Education in the Digital Era”, as the first book that IPMI is actually publishing, it provides a comprehensive exploration of AI's transformative power across these domains. It highlights real-world applications, discusses the societal and ethical implications, and offers insights into how AI can foster progress in diverse fields. In line with the book's theme, the AI Revolution and Meets Sustainability: Driving Impact in 2025, it serves as a platform to delve deeper into the ideas presented in the book. This event aims to connect academics, industry professionals, and policymakers to discuss the broader implications of AI and its practical applications. Through an engaging discussion and sharing session with esteemed guest speakers, the event will provide attendees with valuable insights and actionable strategies for leveraging AI in their respective fields.